Streamlining the flow of production system through elimination the waste of the overburden (muri) for manual handling process - Ani, M.N.C. (IEOM Society, 2019)
In this paper the process improvement activity in a production system towards streamlining the production flow using the PDCA (Plan-Do-Check-Act) model for manufacturing industries was investigated by focusing on the waste of overburden (muri) for manual handling process. Currently the implementation of the continuous improvement in industries has numerous versions focusing on the elimination of the wastes (muda) but less consideration of work on overburden (muri). One of the issues in continuous improvement activity in manufacturing industries is to overlook other wastes as defined by Lean Manufacturing (LM) which are Mura and Muri. Targeting on the optimizing and streamlining the production flow, the detailed steps and processes of PDCA were used in this research based on experiences, knowledges and availability of the data collection. Thus, in this paper, detailed adaptation process for each phase in PDCA was investigated through published literature, current implementation of PDCA in case study industry and performance of the production system in the case study industry. Based on the investigation and implementation of the case study industry, the result shows an adaptation of PCDA in eliminating the waste of overburden (muri) with suitable tools for each phase complements well with the continuous improvement program. The production output as determined through the developed PCDA tools increased by 17.7 by the end of continuous improvement program. Â© IEOM Society International.